Identifying the crosstalk of dysfunctional pathways mediated by lncRNAs in breast cancer subtypes. Issue 3 (4th January 2016) - Wang, Li; Li, Jing; Zhao, Hongying; Hu, Jing; Ping, Yanyan; Li, Feng; Lan, Yujia; Xu, Chaohan; Xiao, Yun; Li, Xia
Abstract : Crosstalk among abnormal pathways widely occurs in human cancer and generally leads to insensitivity to cancer treatment. Abstract : Crosstalk among abnormal pathways widely occurs in human cancer and generally leads to insensitivity to cancer treatment. How long non-coding RNAs (lncRNAs) participate in the regulation of an abnormal pathway crosstalk in human cancer is largely unknown. Here, we proposed a strategy that integrates mRNA and lncRNA expression profiles for systematic identification of lncRNA-mediated crosstalk among risk pathways in different breast cancer subtypes. We identified 12 to 44 crosstalking pathway pairs mediated by 28 to 49 lncRNAs in four breast cancer subtypes. An LncRNA-mediated crosstalking pathway network in each breast cancer subtype was then constructed. We observed a number of breast cancer subtype-specific crosstalks of risk pathways. These subtype-specific lncRNA-mediated pathway crosstalks largely determined subtype-selective functions. Notably, we observed that lncRNAs mediated the crosstalk of pathways by cooperating with known important protein-coding genes, which play core roles in the deterioration of breast cancer. And we also identified key lncRNAs contributing to the crosstalk network in each subtype. As an example, the low expression of LIFR-AS1 was associated with poor survival in LumB subtype, and its cooperated genes IL1R and TGFBR located at the most upstream of the MAPK signaling pathway shared a common cascade path (p38 MAPKs-MEF2C) that can result in proliferation, differentiation and apoptosis. In summary, we offer an effective way to characterize complex crosstalks mediated by lncRNAs in breast cancer subtypes, which can be applied to other diseases and provide useful information for understanding the pathogenesis of human cancer.